Radiological Investigation of the Small Intestine by Small Bowel Enema Technique. Issue 4 (December 1960) - Pygott, F.; Street, D. F.; Shellshear, M. F.; Rhodes, C. J.
Abstract : This paper records some experience with the Scott Harden technique of small intestinal intubation for performing small bowel enemas. It is particularly recommended for searching for obstructive or infiltrative lesions of the small intestine.